Growth Behaviour of Ganoderma lucidum on Different Substrates - , Barsharani Sethi; , Niranjan Chinara (Archives of Current Research International, 2025)
Reishi mushroom (Ganoderma lucidum) is one of the medicinal mushrooms considered as “Elixir of life”. It grows on different agricultural and forest byproducts during rainy season. In order to study the yield potential of Ganoderma lucidum, five locally available substrates such as paddy straw, sugarcane bagasse, maize stalk, saw dust and coir pith were evaluated at Centre of Tropical Mushroom Research and Training (CTMRT), Department of Plant Pathology, College of Agriculture, Odisha University of Agriculture and Technology, Bhubaneswar. Mushroom bags were prepared using processed sterilised substrates. During growth period data on days to spawn run, days to pin head initiation, days to first harvest, biological efficiency (%), average number of fruiting bodies per bag, yield (g/bag), size of pileus (mm) and stipe length (mm) were recorded. The recorded data were analysed with RBD using MS Excel. Among the substrates, highest yield (31.3g) of mushroom was recorded with 15.6% biological efficiency from saw dust followed by coir pith (13.3% BE). However, early spawn run and pinhead formation was recorded from paddy straw substrate with 22.5days and 33.0days respectively. Significantly poor spawn run was observed as in case of sugarcane bagasse with 5.5 per cent biological efficiency. Similarly maximum pileus size 78.0 mm was recorded in mushroom harvested from saw dust followed by paddy straw (55.0mm) and coir pith (52.3mm).